Two ploidy levels of genetically delimited groups of the Calypogeia fissa complex (Jungermanniopsida, Calypogeiaceae) - Buczkowska, Katarzyna; Hornik, Bartosz; Czołpińska, Magdalena (Biodiversity: Research and Conservation, 2015)
Calypogeia fissa is a suboceanic-mediterrean and amphiatlantic species, which comprises two subspecies: C. fissa subsp. fissa occurring in Europe and C. fissa subsp. neogea Schust. known from North America. Recently, within the European part of distribution, three groups (PS, PB and G) were distinguished with the aid of genetic and molecular markers. The flow cytometry results revealed that two of the detected groups of the European C. fissa, which are frequent in Poland (PS and PB), differ in ploidy level: the PS group is haploid, whereas the PB group is diploid. Isozyme pattern at two loci may suggest an allopolyploid origin of the diploid PB group.